2018
DOI: 10.1590/1413-785220182602187215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Muscular Evaluation in Patellofemoral Pain Syndrome

Abstract: Objective:To define a profile of the muscle groups affected by patellofemoral pain syndrome (PFPS) to determine a pattern of functional weaknesses around the knee. Methods:Sixty-three female patients were randomly selected, and 17 included in this study, receiving a clinical evaluation with pre-established protocol which evaluated the quadriceps, abductors, range of motion in the internal rotators and ankle dorsiflexors, pelvic tilt, and dynamic valgus. Results:Losses were seen in abductor strength and ankle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…The average of VMO/VL activation ratio during stepdown activity was lower in participants with PFPS compared to healthy subjects. 43,48,49 These findings may indicate that PFPS may be related to lowered activity of VMO muscle 3 , and the authors also observed that the activity of VMO and VL in healthy females was doubled to enable them to execute the stepdown activity compared to the males. The current study did not find gender differences in VMO/VL activation ratio in healthy subjects, but such differences may be present in subjects with PFPS.…”
Section: Discussionmentioning
confidence: 80%
“…The average of VMO/VL activation ratio during stepdown activity was lower in participants with PFPS compared to healthy subjects. 43,48,49 These findings may indicate that PFPS may be related to lowered activity of VMO muscle 3 , and the authors also observed that the activity of VMO and VL in healthy females was doubled to enable them to execute the stepdown activity compared to the males. The current study did not find gender differences in VMO/VL activation ratio in healthy subjects, but such differences may be present in subjects with PFPS.…”
Section: Discussionmentioning
confidence: 80%
“…A decrease in quadriceps strength displays a direct correlation with the patients’ proprioception and joint function, while a deficiency in gluteus medius strength negatively impacts their gait function. [ 1 , 2 , 6 ] Aghapour et al [ 20 ] showed that KT provides pain relief for PFPS patients. Miller et al [ 44 ] analyzed the range of extension in the affected limb and the range of motion of squatting in PFPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] There are several designations for this ailment, including runner’s knee, anterior knee pain, chondromalacia patella, or patellofemoral pain. [ 2 ] PFPS is a common condition in individuals who engage in regular sports participation and demonstrates higher incidence in women in comparison to men. Numerous studies propose that PFPS contributes to 25 to 40 per cent of all knee problems.…”
Section: Introductionmentioning
confidence: 99%